Sound Body, Sound Mind? Asymmetric and Symmetric Fetal Growth Restriction and Human Capital Development - Joshua J. Robinson (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2014)
This paper explores the causal pathway by which poor fetal health translates into reducing educational attainment and earnings as an adult. Using insights from the medical literature, I decompose low birth weight infants into two distinct subtypes: a symmetric type, which is characterized by cognitive deficits, and an asymmetric type, which exhibits little to no cognitive problems. Using data from a longitudinal survey of newborns, I establish three results: First, there is empirical evidence of brain sparing in the asymmetric subtype, but not in the symmetric subtype. Second, despite differences in cognitive impairment, both subtypes exhibit similar impairment to physical health. And finally, there is evidence that the causes and timing of onset during pregnancy are different for asymmetric and symmetric growth restriction. The results indicate that differentiating between these subtypes may other new opportunities to identify the underlying casual relationships between health and human capital development, as well as uncovering the "black box" mechanism behind the fetal origins hypothesis. These results also have broad implications for the timing of policy interventions aimed at pregnant women.
Keywords: 330